Self-assessment in English language teaching and learning in the current decade (2010-2020): a systematic review - Hosseini, Mona; Nimehchisalem, Vahid (Scientific Research Publishing, 2021)
Self-assessment (SA), defined as the evaluation of process and product and the main feature of self-regulated learning, has been the focus of many recent studies. Due to the importance of SA, the purpose of this systematic review is to provide a comprehensive overview of relevant studies regarding the use of SA for teaching and learning English language. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was employed to collect studies on SA. The search for articles was done with the combination of these keywords: “self-regulation”, “self-assessment”, “foreign language learning”, “student”, and “teachers” in EBSCOhost research platform. We found 106 studies related to SA published in period of 2010-2020. After screening the title and abstracts for selecting articles, based on the inclusion and exclusion criteria, 18 articles were selected to be reviewed. These articles were closely related to the focus of this systematic review on the reliability and validity, effectiveness, accuracy as well as the modes of application of SA in English language learning-teaching. The paper starts with reviewing the definitions of SA and further it analyzes and synthesizes the selected studies to reply to the research questions. The paper concludes with the pedagogical implications and recommendations for future studies on various aspects of SA in the field of English language learning and teaching.